ECM-transmitted shear stress induces apoptotic cell extrusion in early breast gland development - Friedland, F.; Babu, S.; Springer, R.; Konrad, J.; Herfs, Y.; Gerlach, S.; Gehlen, J.; Krause, H.-J.; De Laporte, L.; Merkel, R.; Noetzel, E. (Frontiers in Cell and Developmental Biology, 2022)
Epithelial cells of human breast glands are exposed to various mechanical ECM stresses that regulate tissue development and homeostasis. Mechanoadaptation of breast gland tissue to ECM-transmitted shear stress remained poorly investigated due to the lack of valid experimental approaches. Therefore, we created a magnetic shear strain device that enabled, for the first time, to analyze the instant shear strain response of human breast gland cells. MCF10A-derived breast acini with basement membranes (BM) of defined maturation state and basoapical polarization were used to resemble breast gland morphogenesis in vitro. The novel biophysical tool was used to apply cyclic shear strain with defined amplitudes (≤15%, 0.2 Hz) over 22 h on living spheroids embedded in an ultrasoft matrix (<60 Pa). We demonstrated that breast spheroids gain resistance to shear strain, which increased with BM maturation and basoapical polarization. Most intriguingly, poorly developed spheroids were prone to cyclic strain-induced extrusion of apoptotic cells from the spheroid body. In contrast, matured spheroids were insensitive to this mechanoresponse—indicating changing mechanosensing or mechanotransduction mechanisms during breast tissue morphogenesis. Together, we introduced a versatile tool to study cyclic shear stress responses of 3D cell culture models. It can be used to strain, in principle, all kinds of cell clusters, even those that grow only in ultrasoft hydrogels. We believe that this approach opens new doors to gain new insights into dynamic shear strain-induced mechanobiological regulation circuits between cells and their ECM.